Exploring into methods for component-based software development - Liu, Xinying. (2008)
In this paper, we investigate the component models JavaBean, COM, EJB, and CMM, and propose an extending novel Object-Oriented software development methods for integrating component-based software modeling and component-based software development. The proposed approach involves all the phases of the software life cycle. In the system requirement phase, Use Case Modeling defines the scope of the system. In the system analysis phase, the proposed approach decomposes the overall requirements into continuous processes connected with flow of data through an enhanced data flow diagram (DFD) called data and control flow net (DF Net). Some simple specifications are used to describe the processes. In design and analysis phase, we semi-automatically transform requirements specified in DF Nets into Component-Based implementation.